Design and Simulate Mixing of Compressed Natural Gas with Air in a Mixing Device - K., Kadirgama; M. M., Noor; D., Ramasamy; M. R. M., Rejab (2008)
Gas mixer is a device used to determine the amount of natural gas and air before entering the engine. It injects the gas into the intake air stream of an internal combustion chamber using a combination of radial holes and radial tubes located around the perimeter of an air flow passage. The size of intake air passage, the number and size of the radial holes and tubes varies to achieve adequate gas or air mixing for the particular engine. Measurement of air flow necessary for engine operation is the selection criteria of mixers. The power obtained from engine is dependent on the size of the mixer. It can be seen from the experimental result that a smaller mixer caused higher pressure at the throat in compare to the analytical result. High pressure caused low velocity at the throat. Both smaller and larger mixer was able to promote the methane into the outlet from the inlet tube. Smaller size throat mixer at the throat restricted caused undesirable results.